2006
DOI: 10.1523/jneurosci.3486-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologically Plausible Model of Action Selection and Oscillatory Activity in the Basal Ganglia

Abstract: The basal ganglia (BG) have long been implicated in both motor function and dysfunction. It has been proposed that the BG form a centralized action selection circuit, resolving conflict between multiple neural systems competing for access to the final common motor pathway. We present a new spiking neuron model of the BG circuitry to test this proposal, incorporating all major features and many physiologically plausible details. We include the following: effects of dopamine in the subthalamic nucleus (STN) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
445
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(462 citation statements)
references
References 180 publications
(286 reference statements)
16
445
1
Order By: Relevance
“…Relationship to other models There have been a number of other modeling studies that investigated the oscillations present in the basal ganglia (Gillies et al, 2002;Terman et al, 2002;Humphries et al, 2006;Leblois et al, 2006). Two of those studies (Gillies et al, 2002;) also focused on the STN-GPe circuit and found that it can generate oscillatory activity, but the mechanisms that generated these oscillations were very different from our model, as we now describe.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Relationship to other models There have been a number of other modeling studies that investigated the oscillations present in the basal ganglia (Gillies et al, 2002;Terman et al, 2002;Humphries et al, 2006;Leblois et al, 2006). Two of those studies (Gillies et al, 2002;) also focused on the STN-GPe circuit and found that it can generate oscillatory activity, but the mechanisms that generated these oscillations were very different from our model, as we now describe.…”
Section: Discussionmentioning
confidence: 85%
“…Two other models simulated a more general circuit including the cortex, the basal ganglia, and the thalamus (Humphries et al, 2006;Leblois et al, 2006). Leblois et al (2006) observed oscillatory behavior in theta-alpha band for realistic values of transmission delays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While an interesting hypothesis, this mapping does not account for the microcircuit of the striatum, or the effects of the numerous neuromodulators within it. Other models of the whole basal ganglia circuit do not rely on the local collaterals within striatum for their computations, rather proposing that the striatum is both integrator of diverse cortical information and filter on weak cortical inputs, as the first stage of an input selection mechanism implemented by the whole basal ganglia (as opposed to just the striatum), (Gurney et al, 2001;Humphries et al, 2006) -but these models too do not account for the striatal microcircuit.…”
Section: Introductionmentioning
confidence: 99%